Keberanian dalam Mengambil Keputusan dan Risiko oleh Petani Padi Organik di Kabupaten Bantul - Rahmawati, Nur; Triyono, Triyono (Program Studi Agribisnis, Fakultas Pertanian, Universitas Muhammadiyah Yogyakarta, 2017)
Entrepreneurship on organic farming is often faced with high risks. This study aims to determine the courage of farmer in decision making and risk taking on organic rice farming and to know the factors that influence it. The research was conducted by survey method. Data were collected through interviews to 116 organic rice farmers in Bantul Regency, then analyzed descriptively and regression analysis. The results showed that the courage of farmers in decision making and risk taking on the organic rice farming is strong enough. Age, training, market orientation and cooperation network have a positive effect on the courage of farmer in decision making; while government support has a negative effect. Meanwhile, the courage of farmer in risk taking on organic rice farming is influenced by market orientation.